Navigating Uncertainty: Cutting-Edge Approaches in Process Control and Monitoring for Risk Mitigation in Supply Chain Management - Alok Bihari Singh; Yogesh Mishra; Chandni Dusad; Govind Sharan Dangayach; Prabir Sarkar; Makkhan Lal Meena (Engineering Proceedings)
In today’s dynamic and uncertain environment, supply chains are increasingly vulnerable to disruptions that can negatively impact operational efficiency, cost management, and customer satisfaction. Ensuring supply chain resilience and continuity has become a critical challenge for businesses. This review addresses the pressing issue of supply chain risk management by evaluating cutting-edge solutions that enhance visibility, agility, and responsiveness. Through a comprehensive analysis of literature from 2009 to 2024, sourced from Web of Science, Scopus, and Google Scholar, this study identifies key methodologies, technologies, and frameworks designed to mitigate supply chain risks. The findings of the study highlight the revolutionary potential of IoT sensors, machine learning algorithms, and digital twins for proactive risk assessment and mitigation, offering a pathway to safeguard supply networks in the face of uncertainty.